Lactic acid bacteria with a strong antioxidant function isolated from “Jiangshui,” pickles, and feces - Hu, Yue; Zhao, Yan; Jia, Xu; Liu, Dan; Huang, Xinhe; Wang, Cheng; Zhu, Yanhua; Yue, Changwu; Deng, Shanshan; Lyu, Yuhong (Frontiers in Microbiology, 2023)
Excessive free radicals and iron death lead to oxidative damage, which is one of the main causes of aging and diseases. In this field of antioxidation, developing new, safe, and efficient antioxidants is the main research focus. Lactic acid bacteria (LAB) are natural antioxidants with good antioxidant activity and can regulate gastrointestinal microecological balance and immunity. In this study, 15 LAB strains from fermented foods (“Jiangshui” and pickles) or feces were evaluated in terms of their antioxidant attributes. Strains with strong antioxidant capacity were preliminarily screened by the following tests: 2,2-diphenyl-1-picrylhydrazyl (DPPH), hydroxyl radical, superoxide anion radical scavenging capacity; ferrous ion chelating assay; hydrogen peroxide tolerance capacity. Then, the adhesion of the screened strains to the intestinal tract was examined using hydrophobic and auto-aggregation tests. The safety of the strains was analyzed based on their minimum inhibitory concentration and hemolysis, and 16S rRNA was used for molecular biological identification. Antimicrobial activity tests showed them probiotic function. The cell-free supernatant of selected strains were used to explore the protective effect against oxidative damage cells. The scavenging rate of DPPH, hydroxyl radicals, and ferrous ion-chelating of 15 strains ranged from 28.81–82.75%, 6.54–68.52%, and 9.46–17.92%, respectively, the scavenging superoxide anion scavenging activity all exceeded 10%. According to all the antioxidant-related tests, strains possessing high antioxidant activities J2-4, J2-5, J2-9, YP-1, and W-4 were screened, these five strains demonstrated tolerance to 2 mM hydrogen peroxide. J2-4, J2-5, and J2-9 were Lactobacillus fermentans and γ-hemolytic (non-hemolytic). YP-1 and W-4 were Lactobacillus paracasei and α-hemolytic (grass-green hemolytic). Although L. paracasei has been proven as a safe probiotic without hemolytic characteristics, the hemolytic characteristics of YP-1 and W-4 should be further studied. Due to the weak hydrophobicity and antimicrobial activity of J2-4, finally, we selected J2-5, J2-9 for cell experiment, J2-5 and J2-9 showed an excellent ability that resistant to oxidative damage by increasing SOD, CAT, T-AOC activity of 293T cells. Therefore, J2-5, and J2-9 strains from fermented foods “Jiangshui” could be used as potential antioxidants for functional food, health care, and skincare.